PENGEMBANGAN LKPD BERMUATAN SIKAP ILMIAH DALAM SETTING TAHAPAN DISCOVERY LEARNING SMP - Masliyani, Sintya (Jurnal AlphaEuclidEdu, 2024)
This research aims to produce student worksheet containing scientific attitude in discovery learning phase, arithmetic topics, VII grade SMPN 4 Sungai Raya setting and also to describe the level of validity, prcaiticality, to know the level of student completeness score in the product of student worksheet development. The research method that is used is resource and development (RnD) by adapting Thiagarajan 4D development model. Data source in this research is the result of 3 validators, teacher and student practicality questionnaire, and student worksheet tryouts. Data collection techniques are validators validity questionnaire, practicality questionnaire, student problem test, and documentation of student worksheet used by teacher. The research result showed that during the development of student worksheet containing scientific attitude in discovery learning phase setting was conducted in only 3 phases which are define, design, and development phase. Validity of average percentage of student worksheet in learning aspect was 4.6 or 94% which was in very valid category. In technical/appearance aspect was 4.6 or 92% in very valid category, in compatibility strategy of discovery learning was 4.8 or 97% in very valid category. The practicality utility of student worksheet containing scientific attitude in discovery learning phase setting by teacher was 4.7 in very practical category, and by student was 4.3 in very practical category. The level of completeness in the first tryout was gained in averade percentage of completeness of 100% in very high category and in the second tryout was gained in average percentage of completeness of 87.5% in very high category